Auditory driving of the autonomic nervous system: Listening to theta-frequency binaural beats post-exercise increases parasympathetic activation and sympathetic withdrawal - McConnell, Patrick A.; Froeliger, Brett; Garland, Eric L.; Ives, Jeffrey C.; Sforzo, Gary A. (Frontiers in Psychology, 2014)
Binaural beats are an auditory illusion perceived when two or more pure tones of similar frequencies are presented dichotically through stereo headphones. Although this phenomenon is thought to facilitate state changes (e.g., relaxation), few empirical studies have reported on whether binaural beats produce changes in autonomic arousal. Therefore, the present study investigated the effects of binaural beating on autonomic dynamics (heart-rate variability (HRV)) during post-exercise relaxation. Subjects (n = 21; 18-29 years old) participated in a double-blind, placebo-controlled study during which binaural beats and placebo were administered over two randomized and counterbalanced sessions (within-subjects repeated-measures design). At the onset of each visit, subjects exercised for 20-min; post-exercise, subjects listened to either binaural beats (‘wide-band’ theta-frequency binaural beats) or placebo (carrier tone) for 20-min while relaxing alone in a quiet, low-light environment. Dependent variables consisted of high frequency (HF, reflecting parasympathetic activity), low frequency (LF, reflecting sympathetic and parasympathetic activity) and LF/HF normalized powers, as well as self-reported relaxation. As compared to the placebo visit, the binaural beat visit resulted in greater self-reported relaxation, as well as increased parasympathetic activation and sympathetic withdrawal. By the end of the 20-min relaxation period there were no observable differences in HRV between binaural beat and placebo visits, although binaural-beat associated HRV significantly predicted subsequent reported relaxation. Findings suggest that listening to binaural beats may exert an acute influence on both LF and HF components of HRV and may increase subjective feelings of relaxation.